Correlation of Various Levels of Body Mass Index to Vascular Endothelial Growth Factor-A - Permana, Noah Jefferson; Lesmana, Ronny; Setiawan, Setiawan; Lubis, Leonardo; Rosdianto, Aziiz Mardanarian; Rejeki, Purwo Sri (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Obesity, reflected by high body mass index (BMI) value, has become a global health concern. Both obesity and vascular endothelial growth factor-A (VEGF-A) are major risk factors for cardiometabolic diseases. Although many studies have shown that obesity induces angiogenesis through increased VEGF-A, there remains a gap regarding the correlation between BMI categories and VEGF-A levels. This study aimed to analyze the correlation between various level of BMI and VEGF-A concentrations.Methods: This cross-sectional in vivo study analyzed blood samples from 90 adults enrolled in the Universitas Padjadjaran Wellness Program ( December 2022–June 2023) selected using simple random sampling.VEGF-A concentrations were measured using multiplex ELISA assays. Data normality was assessed using the Kolmogorov-Smirnov test. Differences between BMI groups were analyze with ANOVA, and correlations were evaluated using Pearson’s test. Results: Of the 90 samples, 62 were included, and were grouped as normal weight (29%), overweight (32.2%), obesity class I (30.6%), obesity class II (6.4%), and obesity class III (1.6%). Mean VEGF-A concentrations showed an increasing trend with higher BMI, though differences between groups were not statistically significant (p=0.482). A weak positive correlation was observed between BMI and VEGF-A levels (r=0.267; p=0.036).Conclusion: Higher BMI is associated with higher VEGF-A, indicating obesity-induced inflammation and angiogenic activity. These findings highlight the importance of weight control through balanced diet and physical activity to mitigate long-term risks of cardiometabolic and chronic diseases.